A Controller Design for a Stability Improvement of an Integrated Charging System in Hybrid Electric Vehicle. Issue 4 (2019) - Kang, Ho-Sung; Kim, Seok-Min; Bak, Yeongsu; Lee, Kyo-Beum
Abstract: This paper proposes a controller design for a stability improvement of an integrated charging system in hybrid electric vehicle (HEV). Conventional HEVs include a starter generator system, which consists of generator and its drive inverter. Contrary to them, the proposed integrated charging system operates as a generator drive system and bi-directional battery charging system by installing some power relays and additional circuit in general HEVs. Therefore, the integrated charging system results in reduced system components in HEV by eliminating on-board charger (OBC), also the weight and system volume can be decreased. In addition, a feed-forward compensation method is proposed to improve the transient states characteristics of the battery charging system in this paper. The effectiveness and validity of proposed design and control method for the integrated charging system is verified by simulation results.